Educational and Language Philosophy Principle: Content Analysis on â€œBasic English Handoutâ€ - Yulia Agustina; Darmiyati Zuchdy (Universitas Hamzanwadi, 2020)
Educational and language philosophy compact between education and language philosophy. Education philosophy seeks the truth in education section. While, language philosophy is combination between linguistics and philosophy. Hence, language is as a vital medium in philosophyzing. The research was aimed to acertain the educational and language philosophy principle. This research used content analysis inferential. The data resource was ‘Basic English Handout’ for the first semester students of Early Childhood Education Program of Hamzanwadi University. The data were collected by: data making, data reduction, inference, and analyzing the data. To ascertain valid and reliable data used semantic validation data and test-retest reliability. The researchers used analytical construct with qualitative conceptual domain in analyzing data. The results showed that educational and language philosophy principle on ‘Basic English Handout’ were: existentialism, reconstructionism, and humanism. Existentialism reffered to students’ activities on: committing oneself in learning concrete experience, dynamic, reflection observation, active experimentation, and creating thinking conceptualization. While, reconstructionism created students on: problem solving, focusing on transformation (direct participation), democracy, learning by doing, cooperation in learning and doing the exercises. Last, humanisme instructed students to: think inductively, explore and develop self-concept, develop own experience and trials, actively participating, and dicipline in learning activities.